Polyvinylidene Fluoride Mesh Use in Laparoscopic Ventral Mesh Rectopexy in Patients with Obstructive Defecation Syndrome for the First Time. Issue 10 (17th September 2021) - Alemrajabi, Mahdi; Darabi, Behnam; Banivaheb, Behrouz; Hemmati, Nima; Jahanian, Sepideh; Moradi, Mohammad
Abstract: Background: Obstructive defecation syndrome (ODS) affects quality of life of patients to a great extent by disturbing defecation. Laparoscopic ventral mesh rectopexy (LVMR) has gained much attention in the recent years. Common synthetic used meshes have a risk of erosion for adjacent pelvic organs leading to some complications. The aim of this study was to assess the outcomes of LVMR using polyvinylidene fluoride (PVDF) mesh in patients with ODS for the first time. Methods and Materials: In this experimental study, patients with a history of ODS and associated signs and symptoms such as descending perineum, rectocele, enterocele, intussusception, rectal prolapse or a combined disorder were recruited. The patients underwent LVMR using a PVDF mesh. They were followed using the Constipation Scoring System (CSS) score. Participants were followed up for 12 months after surgery. Complications and CSS for each patient and its changes were the main outcomes of this study. Results: Of 156 patients, 155 had a 12-month complete follow-up. Thirty-nine (25.2%) were male and 116 (74.8%) female. Mean ± SD age of participants was 45.61 ± 14.02 years. The overall complication rate was 3.87%. No major mesh-related complications were recorded. Four cases (2.58%) of trocar site hernia were reported. Also, two cases (1.29%) of postoperative bleeding occurred. CSS before the operation and 1, 3, and 12 months after it were 11.04 ± 5.93, 7.98 ± 4.85, 5.46 ± 3.70 and 4.09 ± 2.98, respectively ( p  < 0.001). Conclusion: Synthetic meshes might cause severe erosion in pelvic organs. However, at least in short-term follow-up, PVDF mesh seems to be safe and effective in LVMR, with the advantage of being cheaper.